Effects of carnosine supplementation on glucose metabolism: Pilot clinical trial. Issue 5 (4th April 2016) - de Courten, Barbora; Jakubova, Michaela; de Courten, Maximilian PJ; Kukurova, Ivica Just; Vallova, Silvia; Krumpolec, Patrik; Valkovic, Ladislav; Kurdiova, Timea; Garzon, Davide; Barbaresi, Silvia; Teede, Helena J.; Derave, Wim; et al.
Abstract : Objective: Carnosine is a naturally present dipeptide in humans and an over‐the counter food additive. Evidence from animal studies supports the role for carnosine in the prevention and treatment of diabetes and cardiovascular disease, yet there is limited human data. This study investigated whether carnosine supplementation in individuals with overweight or obesity improves diabetes and cardiovascular risk factors. Methods: In a double‐blind randomized pilot trial in nondiabetic individuals with overweight and obesity (age 43 ± 8 years; body mass index 31 ± 4 kg/m 2 ), 15 individuals were randomly assigned to 2 g carnosine daily and 15 individuals to placebo for 12 weeks. Insulin sensitivity and secretion, glucose tolerance (oral glucose tolerance test), blood pressure, plasma lipid profile, skeletal muscle ( 1 H‐MRS), and urinary carnosine levels were measured. Results: Carnosine concentrations increased in urine after supplementation ( P < 0.05). An increase in fasting insulin and insulin resistance was hampered in individuals receiving carnosine compared to placebo, and this remained significant after adjustment for age, sex, and change in body weight ( P = 0.02, P = 0.04, respectively). Two‐hour glucose and insulin were both lower after carnosine supplementation compared to placebo in individuals with impaired glucose tolerance ( P < 0.05). Conclusions: These pilot intervention data suggest that carnosine supplementation may be an effective strategy for prevention of type 2 diabetes.